The Minimalistic Malignancy- Low grade Fibromyxoid Sarcoma - Anubha Bajaj (Journal of Clinical and Diagnostic Pathology, 2020)
Low grade fibromyxoid sarcoma (LGFMS) is an exceptional, low grade, soft tissue sarcoma with indolent biological behaviour, extensive preclinical stage, enhanced localized tumour reoccurrence and delayed, distant metastasis. As the deceptively benign neoplasm was initially scripted by Evans in 1987, the tumefaction is nomenclated as “Evan’s tumour”. Incidence of sarcomas is nearly 1% of adult malignancies wherein low grade fibromyxoid sarcoma represents roughly beneath <5% of soft tissue sarcomas 1.
Keywords: Low Grade Fibromyxoid Sarcoma